The Intimidation of Trainers: Prompting Martial Arts Athletes to Practice - Fitri, Mustika; Gumelar, Moch Insan (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2020)
Rough and harsh trainings often occur in sports training, one of which is in the martial arts sport where athletes often received more intimidation from the trainer than in other sports. Therefore, the aim of this study was to explore the form of intimidations occur in the trainer-athlete relationship as an attempt to increase the training motivation. The method used in this research was a grounded theory approach. Observations and interviews were conducted to collect data. The result of this study found that intimidation needs to be done by trainers. However, trainers must be able to choose when to intimidate the athletes and have to understand the athletes’ acceptance whether it has a positive or a negative impact.